Advancing layered cathode material's cycling stability from uniform doping to non-uniform doping. Issue 32 (4th August 2020) - Wang, Kuan; Yan, Pengfei; Wang, Zelin; Fu, Junjie; Zhang, Zhenlu; Ke, Xiaoxing; Sui, Manling
Abstract : Dopant segregation induced precipitates can further improve the cycling stability of a P2-layered cathode due to the precipitation strengthening effect, which conceptually validates that non-uniform doping has big advantage over uniform doping. Abstract : Uniform doping has been recognized as an effective approach to improve the cycling performance of many layered cathodes. Herein, we propose non-uniform doping as a more effective approach to enhance the cycling stability of layered cathodes via the precipitation strengthening mechanism. In this work, we investigate four doped (Cu, Ti, Mg, and Zn) P2-layered cathodes for sodium ion batteries and validate that cycling induced dopant segregation can substantially enhance the cyclability due to mitigation of bulk cracking. Our comprehensive analysis indicates that dopant evolution is quite diverse during electrochemical cycling, not only depending on the nature of each dopant but also the cycling conditions applied. The migration and segregation behaviors of inactive dopants demonstrate the complex dynamics within grain bulk during battery cycling, which also offers us chances to engineer the physicochemical properties of layered cathodes. Non-uniform doping opens a new avenue for designing battery materials with superior mechanical properties.